#TITLE_ALTERNATIVE# - PRABHAWA (NIM 13204112); Pembimbing : Dr. Ir. Pekik Argo Dahono dan Dr. Eng. Estiko Rijanto, LUHUR
The purpose of this project is to design a digital PI controller for synchronous generator voltage regulation. The designed controller is validated through on-line simulation. It means that the PI algorithm is downloaded to a microcontroller and it is then connected to a PC containing generator model to simulate the control system performance in real time manner. PCI card is used as an interface between the PC and the microcontroller as well as the oscilloscope. The fourth order nonlinear transient model of synchronous generator is used. The Linearization procedure is applied to design the controller. Then, the fourth order linier model is reduced by balanced residualization method. Finally, the pole placement method is used to determine the proportional and integral gain.